Spousal sexual violence, sexual behavior and sexually transmitted infections among ever-married women in Uganda - Ojiambo Wandera, Stephen; Ntozi, James P. M.; Kwagala, Betty (African Population Studies, 2010)
Despite the increasing recognition of the significance of spousal sexual violence in developing countries, evidence on its consequences for reproductive health remains limited. The aim of the paper was to examine the relationship between spousal sexual violence (SSV) and sexually transmitted infections (STIs) using a sample of 1749 ever-married women, from the 2006 Uganda Demographic and Health Survey. Pearson Chi-square tests and binary logistic regressions were used to investigate associations between SSV, STIs and selected reproductive health outcomes. From the analyses, 25% and 15% of ever-married women experienced SSV and reported STIs, respectively in the last 12 months. Women who experienced SSV were twice more likely to have had STIs in the last 12 months compared to those who did not. SSV is an important social and public health problem having implications on women's reproductive health and interventions to improve it should directly address the issue of spousal sexual violence.
Keywords: Spousal sexual violence; sexual behaviour; sexually transmitted infections